Special education in Poland (until 1989) – historical perspective - KULBAKA, JACEK (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Jacek Kulbaka, Special education in Poland (until 1989) – historical perspective. Interdisciplinary Contexts of Special Pedagogy, no. 27, Poznań 2019. Pp. 117–149. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/10.14746/ikps.2019.27.06 The article is dedicated to presenting the information regarding the origins, organisation and the activity of special schools and institutions in Europe, with the particular focus on Polish territories (from the beginning of the 19th century to the final years of the Polish People’s Republic). The text nature may be included within the framework of inquiries regarding the history of education. Referring to the wide historical context (social, political, economical, legal, outlook and other determinants), the aim of the author of the text was to introduce the accomplishments of particular individuals, and various institutions active for the children with disabilities, in the discussed period.